“ARTIFACTS OF STONE AND POTTERY”: AN ANALYSIS OF THE LINN SITE (IAS U-28) COLLECTION AT THE MILWAUKEE PUBLIC MUSEUM - (:unkn) unknown (My University, 2023)
This thesis focuses on an understudied archaeological collection at the Milwaukee Public Museum (MPM) from the Linn Site (IAS U-28) in southern Illinois, acquired in the 1930s. Using archaeological methods and archival research, the research aims to characterize the collection's physical attributes and temporal and period affiliations and to contextualize it. This is accomplished through detailed analyses of ceramics and other materials, as well as comparison with other collections from the Linn Site, demonstrating the value of collections-based research. The significance of the research lies in utilizing unstudied materials as archaeological sites disappear. The research highlights ethical tensions and interpersonal conflicts, while addressing gaps in the archaeological literature for the area around the Mississippi and Ohio River confluence. Overall, this research offers valuable insights into archaeological and historical knowledge, emphasizing the importance of studying existing museum collections.